Comparative measurement of short-term fluoride release and inhibition of caries around restoration by ion releasing restorative materials: an in vitro study - Eman T. El-Adl; Maha M. Ebaya; El-Sayed E. Habib; Nadia M. Zaghloul (Scientific Reports)
Abstract The main objective of the current study is to compare short-term fluoride release of three ion releasing restorative materials and assess their inhibitory effect on secondary caries. Materials used in this study included, Self-adhesive hybrid composite (group A), Ion releasing flowable composite liner (group B), and alkasite restorative material (group C). Twenty-two discs were fabricated from each material for short-term fluoride release test, conducted on days 1, 7, and 14. For assessing secondary caries inhibition, sixty-six sound molar teeth were used and standardized class V cavities were prepared. Teeth were divided into three groups according to each material, followed by 800 cycles of thermocycling. Subsequently, teeth were immersed in a solution containing cariogenic bacteria for 30 days. After that, teeth were sectioned bucco-lingually and analyzed using a polarized light microscope to measure inhibition area, outer lesion depth, and extension. Data was statistically analyzed using different tests. The study results revealed a statistically significant differences in fluoride release existed among materials. Self-adhesive hybrid composite exhibited the highest fluoride release. Lesion extension and depth were statistically significantly greater next to Ion-releasing flowable composite liner. The inhibition areas next to the Self-adhesive hybrid composite were statistically significantly larger than the other two materials. In conclusion, all tested ion-releasing restorative materials displayed fluoride release and the potential to inhibit secondary caries formation. Self-adhesive hybrid composite demonstrated the highest fluoride-releasing potential and the greatest ability to inhibit secondary caries. Conversely, Ion-releasing flowable composite liner exhibited the least fluoride release with minimal secondary caries inhibition. Increasing fluoride release correlated with larger inhibition areas and reduced outer lesion depth and extension.